A Panel Approach: How Does Government Expenditure Influence Human Development Index? - Anisa Fadilah; Candra Fajri Ananda; David Kaluge (Jurnal Ekonomi dan Studi Pembangunan, 2018)
This study investigates the influence of government spending on education index, health index, income index of regional, under-develop and develop governments in East Java, Indonesia. In addition, this paper estimates the influence of government spending on the development of cities and districts in East Java. This study applied a quantitative approach by using the Fixed Effect Model and Random Effect Model as the panel data analysis method. There were 38 cities and districts used as the analysis units during 2010-2015. The findings showed that government spending on education, health, and economic has a positive significant influence on every component of human development index. In addition, government spending on infrastructure has a significant influence on the education index and income index yet it does not significantly influence the health index. Furthermore, this study provided the different results of government spending on under-developed and developed regions. Keywords: Government Spending, Human Development Index, Education IndexJEL Classification: H72; I31